Extrusion foaming of poly(ethylene terephthalate) with carbon dioxide based on rheology analysis. (May 2016) - Fan, Chaoyang; Wan, Chen; Gao, Feng; Huang, Chao; Xi, Zhenhao; Xu, Zhimei; Zhao, Ling; Liu, Tao
Although low density poly(ethylene terephthalate) foams take advantage of the combination of good performances and lightness and have a wide range of engineering applications, extrusion foaming of the poly(ethylene terephthalate) is still faced with many challenges, especially the inadequate rheological characteristics. In this work, the melt strength of four types of poly(ethylene terephthalate) was compared on the basis of the analysis on the dynamic complex viscosity, storage and loss modulus, relaxation spectrum, loss factor and extensional viscosity using rheometer. It was found that the two long chain branching poly(ethylene terephthalates) owned overall higher melt viscosity and greater elasticity than the other two linear ones. Furthermore, only one long chain branching poly(ethylene terephthalate), i.e. PET4, succeeded in the extensional viscosity characterization and showed the phenomenon of strain hardening. Thereafter, PET4 was successfully applied for the extrusion foaming with CO2 as the blowing agent. The effects of the foaming temperature, screw revolution speed, gas input and addition of nucleation agent were carefully investigated on the extrusion foaming and the resulted poly(ethylene terephthalate) foams properties. Under the optimization condition, the extruded poly(ethylene terephthalate) foams were produced with the volume expansion ratio of 9.5, average cell size of 265 µm, cell density of 4.58 × 10 5  cells/cm 3 and a narrow cell size distribution.